Pengalaman, Pelayanan, dan Kebahagiaan dalam Perjalanan Kereta Api - Pratiwi Sabrina Lestari; Irena Novarlia; Oman Sukirman (Yayasan Literasi Sains Indonesia, 2026)
This study aims to describe the meaning of tourists’ experiences, the importance of service, and the sense of happiness that emerges when traveling by train at Bandung Station. The study is grounded in the role of transportation not only as a means of mobility, but also as a medium that shapes emotional experiences and impressions for travelers. A qualitative descriptive method with a case study approach was employed. Data were collected through interviews with 12 informants, consisting of 8 long-distance and local train passengers, 3 station officers, and 1 station manager, as well as through planned observations and document analysis. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with NVivo software used as a supporting analytical tool. The findings indicate that train travel is perceived as a comfortable and memorable experience. Service is understood as a form of assistance that provides convenience and a sense of security, while happiness arises from a smooth journey and a clean, well-organized station environment. This study is expected to contribute to efforts in maintaining and improving service to strengthen the positive image of tourism through the strategic role of Bandung Station.